The accuracy of ultrasound as screening method in evaluation of blunt abdominal injury in Alwahda Hospital, Derna (2000-2005) - Habil, Salah; Alshallwi, Abdulbassit; Elzawi, Ibrahim (Al-Mukhtar Journal of Sciences, 2015)
Being non-invasive, repeatable, cheap, and portable, ultrasound scan is increasing becoming a mainstay method to detect injury and bleeding in blunt abdominal trauma. A prospective review of blunt trauma sonograms obtained from January 2000 to December 2005 was carried out. A total of 2160 blunt trauma sonograms were obtained, and 302 patients (14%) had intra abdominal injuries, The mean age was 33.7 ± 19.1 years (range 2-85 years), with 217 (82%) male and 85 (28%) female. There were 275 true –positive, 93 false negative, 43 false positive, and 1749 true-negative findings. Sensitivity of sonography for detecting all intra-abdominal Injuries were 74%, and specificity was 97.6%, Positive Predictive Value 94.4%, Negative Predictive Value 99.2%, Accuracy 99%. We believe that US is an excellent screening modality in the setting of blunt abdominal trauma, but it should be used only where a period of clinical observation is part of the trauma protocol. The limitations of US must be recognized, and considered in Ultrasound based decision in blunt abdominal trauma patient management. Because of its high negative predictive value, we recommend that clinical follow up is adequate for patients whose US results are negative for intra abdominal organ injury. Hypotensive patients screened in the emergency department with positive FAST findings may be triaged directly to therapeutic laparotomy.